Interpreting Revelation and other apocalyptic literature an exegetical handbook - Pate, C. Marvin 1952- (Grand Rapids, MI Kregel Academic, 2016)
The genre and figures of speech of apocalyptic literature -- The historical background of prophetic-apocalyptic books -- The function of apocalypticism and the theme of Israel's story -- Preparing to interpret the text -- Interpreting biblical apocalyptic literature -- Communicating a passage in Revelation -- From text to sermon : two examples -- Selected sources.
Includes bibliographical references (pages 221-232)
Keywords: Bible -- Criticism, interpretation, etc; Bible; Criticism, interpretation, etc